Weight regain: No link to success in a real-life multiday boxing tournament - Reale, R.; Cox,G. R.; Slater, G.; Burke, L. M. (International Journal of Sports Physiology and Performance, 2017)
Purpose: Combat-sport athletes acutely reduce body mass (BM) before weigh-in in an attempt to gain a size/strength advantage over smaller opponents. Few studies have investigated these practices among boxers and none have explored the impact of this practice on competitive success.